2016
DOI: 10.1021/acschembio.5b00967
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Basis of Vitamin A3 Production in Arthropod Vision

Abstract: Metazoan photochemistry involves cis-trans isomerization of a retinylidene chromophore bound to G protein coupled receptors. Successful production of chromophore is critical for photoreceptor production and survival. For chromophore production, animals have to choose from more than 600 naturally occurring carotenoids and process them by oxidative cleavage and geometric isomerization of double bonds. Vertebrates employ three carotenoid cleavage oxygenases to tailor the carotenoid precursor in the synthesis of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Despite recent evidence of RA implications in the development of insects, few studies addressed the link between RA and the carotenoid-retinoid metabolism. So far, NinaB, an isomeroxygenase that combines carotene oxygenase and retinoid isomerase functions, was found in several insect species 40 and appears to use many carotenoids such as α/β-carotene, β-cryptoxanthin, lutein and zeaxanthin as substrates in order to produce various proportions of RALD isomers 40 , 41 . In D. melanogaster , short chain dehydrogenases (SDRs) were shown to be biochemically similar to the human Rdh12 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite recent evidence of RA implications in the development of insects, few studies addressed the link between RA and the carotenoid-retinoid metabolism. So far, NinaB, an isomeroxygenase that combines carotene oxygenase and retinoid isomerase functions, was found in several insect species 40 and appears to use many carotenoids such as α/β-carotene, β-cryptoxanthin, lutein and zeaxanthin as substrates in order to produce various proportions of RALD isomers 40 , 41 . In D. melanogaster , short chain dehydrogenases (SDRs) were shown to be biochemically similar to the human Rdh12 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Using these models of the four CSPs we then performed docking simulations with β-carotene, 3-hydroxyretinol and 3-hydroxyretinal (the visual pigments used by insect instead of retinol and retinal used by vertebrates 43) and found that all three molecules can fit well inside the binding pockets.…”
Section: Resultsmentioning
confidence: 99%
“…In other species, a single enzyme can perform the functions of BCO1, BCO2, and RPE65. Arthropods encode a single carotenoid cleavage enzyme, NinaB, that performs the functions of all three BCO family members (34). Carotenoid cleavage enzymes in lower organisms have a range of substrate specificities.…”
Section: Discussionmentioning
confidence: 99%